Incident Rate of Vesicovaginal Fistula at Dr. Kariadi General Hospital Semarang in 2022 - Zunaidhi Bahar, Rully; Arya Putra, Aditya; Agung Nugroho, Eriawan; Wiryawan Cahyono, Chemmy; Erwinanto, Erwinanto; Santosa, Ardy; Sindhu Wibisono, Dimas; Daniswara, Nanda; Rais Addin, Sofyan (Diponegoro International Medical Journal, 2023)
Background: Vesicovaginal fistula (VVF) is an abnormal connection between the vesicourinaria and the vagina which causes urine to continuously leak through the vagina. The etiology of VVF fistulas has changed from being obstetric to being more hysterectomy related. While management is as early as possible appropriately and prevents further complications that can occur. Aim: Analyzing the comparison of the characteristics of patients with VVF at Dr. Kariadi General Hospital Semarang in 2022.Methods: The study design in this study was a retrospective descriptive observational study. Results: During the period from 3 January to 30 December 2022, 20 patients were found with VVF. Based on the data obtained, the average age of the patients was 39.4 years. Parity in the study subjects consisted of 2 nulliparas (10%), 5 primiparas (25%) and 13 multiparas (65%). Types of fistulas in patients included 14 fistulas after gynecological surgery (70%), 4 fistulas after caesarean section (20%), 1 fistula after radiotherapy (5%) and 1 fistula after trauma (5%). Conclusion: VVF incident in Dr. Kariadi General Hospital Semarang in 2022 were 20 cases with the majority of fistula types after gynecological surgery as many as 14 cases.